Proliferation Assay Using Cryopreserved Porcine Peripheral Mononuclear Cells Stimulated With Concanavalin A and Analyzed With FCS ExpressTM 7.18 Software - Marlene Bravo-Parra; Rahul Nelli; Lu Yen; Gino Castillo; Juan Mora-Díaz; Ana Castillo-Espinoza; Luis Giménez-Lirola (Bio-Protocol)
In vitro lymphocyte proliferation assays are essential for assessing immune responses and antiproliferative drug efficacy. Such assays rely on antigen presentation or mitogen stimulation, with performance determined by reagent concentration and incubation time. Although splenocytes are often used, peripheral blood mononuclear cells (PBMCs) offer more accessible and practical sampling. However, a streamlined protocol for porcine PBMCs proliferation with robust batch analysis has been lacking. We therefore developed a detailed workflow for inducing proliferation in cryopreserved porcine PBMCs using 5 μg/mL concanavalin A (ConA). The protocol covers cell isolation, cryopreservation, ConA stimulation, CD4+ T-cell staining, flow cytometry acquisition and gating on an Attune NxT instrument, and batch analysis with FCS ExpressTM 7.18. This approach yielded 78.9% viable cells, of which 33.8% were CD4+ lymphocytes. Moreover, 93.9% (n = 216) of cells proliferated, yielding up to nine cell generations. Batch analysis in FCS ExpressTM enhanced the accuracy and interpretation of proliferation metrics. This validated protocol provides a reliable framework for generating consistent proliferation data in porcine immunology studies.